Enforcement and Protection of Human Rights Law (HAM) Against Human Trafficking Cases in Indonesia - Nur Angraini, Peggy Dian Septi (Journal of Law Science, 2025)
Law enforcement on human trafficking as part of human rights is linked to theories of substance, structure, legal culture and legal protection. Normative juridical is research originating from a statutory and case approach through secondary data with library value analyzed deductively qualitatively. Enforcement and legal protection of trafficking in persons in Decision Number 215/Pid.Sus/2021/PN.Idm relating to the substance that eradicates trafficking in persons in Law Number 21 of 2007, protecting people with Indonesian migrant work in Law Number 18 Years, and the Criminal Code. Legal structure Defendant I was imprisoned for a period of 4 years and Defendant II for 6 months, accompanied by a fine of Rp. 200,000,000.00, as well as restitution of Rp. 64,075,867.5. The police and the Victim Witness Protection Agency asked for information from the victim and the Indonesian Embassy in Turkey helped the victim return home to Indonesia. The legal culture lacks government oversight and victims are unaware of the threat of human trafficking, recruiting and exploiting victims to other countries for profit.